Intestinal micropatches for oral insulin delivery. (9th August 2017) - Banerjee, Amrita; Wong, Jessica; Gogoi, Rohan; Brown, Tyler; Mitragotri, Samir
Abstract: Diabetes mellitus has become a major public health issue that has almost reached epidemic proportions worldwide. Injectable insulin has been typically utilized for the management of this chronic disease. However, lack of patient compliance with injectable formulations has spurred the development of oral insulin formulations, which although appealing, face several delivery challenges. We have developed novel mucoadhesive intestinal patches, several hundred micrometers in dimension (micropatches) that address the challenges of oral insulin delivery. The micropatches adhere to the intestinal mucosa, release their drug load rapidly within 30 min and are effective in lowering blood glucose levels in vivo . When insulin-loaded micropatches were administered with a permeation enhancer and protease inhibitor, a peak efficacy of 34% drop in blood glucose levels was observed within 3 h. Efficacy further improved to 41% when micropatches were administered in multiple doses. Here, we describe the design of micropatches as an oral insulin formulation and report their in vivo efficacy.